2018
DOI: 10.1159/000490002
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: A Contributor to Depressive Comorbidity in Inflammatory Skin Disease

Abstract: The prevalence of affective disorders such as depression and anxiety is particularly high in patients with autoimmune diseases, including inflammatory skin diseases such as psoriasis, atopic dermatitis, and hidradenitis suppurativa. A dysregulated immune response has been linked to the precipitation of depression in many patient populations. However, studies examining the extent to which the underlying skin disease inflammatory processes contribute to depression and a subsequent decline in quality of life are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 55 publications
0
54
0
2
Order By: Relevance
“…One might speculate that itch, skin pain and sleep disturbances in combination with typical AE skin lesions, cause psychologic distress which may result in development of depression, anxiety and/or impaired QoL . There is still debate whether the depressive and anxious symptoms result from physical discomfort and psychosocial burden of the skin disease or whether these disorders are based on shared inflammatory pathomechanisms …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One might speculate that itch, skin pain and sleep disturbances in combination with typical AE skin lesions, cause psychologic distress which may result in development of depression, anxiety and/or impaired QoL . There is still debate whether the depressive and anxious symptoms result from physical discomfort and psychosocial burden of the skin disease or whether these disorders are based on shared inflammatory pathomechanisms …”
Section: Discussionmentioning
confidence: 99%
“…50,51 There is still debate whether the depressive and anxious symptoms result from physical discomfort and psychosocial burden of the skin disease or whether these disorders are based on shared inflammatory pathomechanisms. 10,52,53 Further investigations are needed to investigate therapeutical effects of new or upcoming treatment options for AE on mental health in AE patients. 54 Trial results from phase 3 dupilumab, a monoclonal antibody against interleukin 4, showed that the proportion of patients with moderate-to-severe AE who reported depression and anxiety was significantly reduced in the active arm compared to the placebo arm.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review spanning across the fields of psychology, neuroscience and dermatology was conducted to gather evidence for the role of inflammation in precipitation of affective disorders in HS patients. Elevated levels of circulating cytokines such as interleukin‐6 (IL‐6) and tumor necrosis factor alpha (TNF‐alpha) may exhibit a dose‐response pattern with severity of depression …”
Section: Oral Presentation 1: Epidemiology Co‐morbiditiesmentioning
confidence: 99%
“…Elevated levels of circulating cytokines such as interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-alpha) may exhibit a dose-response pattern with severity of depression. [12] Pain and distress are core components of the HS experience. [13] This issue was investigated in 201 patients from the Montefiore HS Treatment Center utilizing validated questionnaires.…”
Section: Delaram Frazanfar Yekta Dowlati Lars French Michelle Lowementioning
confidence: 99%
“…The chronic inflammatory processes associated with allergic disorders, as e.g. atopic dermatitis, are even discussed to be linked to psychological comorbidities such as depression [4]. The pathomechanisms of allergic diseases are still unclear [5], and except for antigen avoidance there is no causal therapy.…”
Section: Introductionmentioning
confidence: 99%